2017
DOI: 10.1038/s41598-017-00223-7
|View full text |Cite
|
Sign up to set email alerts
|

Weaning age influences the severity of gastrointestinal microbiome shifts in dairy calves

Abstract: Ruminants microbial consortium is responsible for ruminal fermentation, a process which converts fibrous feeds unsuitable for human consumption into desirable dairy and meat products, begins to establish soon after birth. However, it undergoes a significant transition when digestion shifts from the lower intestine to ruminal fermentation. We hypothesised that delaying the transition from a high milk diet to an exclusively solid food diet (weaning) would lessen the severity of changes in the gastrointestinal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 48 publications
9
90
2
2
Order By: Relevance
“…Eckert et al (2015) also showed that delayed weaning promoted beneficial effects on intake and growth in dairy cows during their weaning and thereafter. This delay in weaning clearly facilitated a more gradual shift in microbial diversity in both the rumen and feces of the dairy calves when feeding a high plane of preweaning nutrition (Meale et al, 2017).…”
Section: Intake and Growth Performancementioning
confidence: 99%
“…Eckert et al (2015) also showed that delayed weaning promoted beneficial effects on intake and growth in dairy cows during their weaning and thereafter. This delay in weaning clearly facilitated a more gradual shift in microbial diversity in both the rumen and feces of the dairy calves when feeding a high plane of preweaning nutrition (Meale et al, 2017).…”
Section: Intake and Growth Performancementioning
confidence: 99%
“…The gut microbiota of mammals, such as pigs, has numerous roles benefiting the host, including maintenance of physiological functions of the intestinal villi, regulation of immune responses, protection from pathogenic bacteria, digestion and fermentation of carbohydrates and production of vitamins [3]. Furthermore, a recent report demonstrated that weaning induced a shift in the intestinal microbiome due to abrupt dietary shifts [4]. During the suckling period, milk provides an environment for the population of Lactobacillus.…”
Section: Introductionmentioning
confidence: 99%
“…S5a). These developmental features have already been described for calves with the same characteristics (age, sex, and breed) fed milk replacers [10], as well as for females of the same breed in Canada [10,13], the USA [14,15], and Japan [16] and for dairy calves of a different breed in Austria [17]. These shared ndings suggest that the fecal microbiota of calves undergoes a predictable age-dependent trend that is common to distinct calf populations.…”
Section: Discussionmentioning
confidence: 54%